User requirements for the development of smartphone self-reporting applications in healthcare - Craven, Michael P.; Selvarajah, Kirusnapillai; Miles, Robert; Schnädelbach, Holger; Massey, Adam; Vedhara, Kavita; Raine-Fenning, Nick; Crowe, John (2013)
Two case studies of the development of Smartphone self-reporting mHealth applications are described: a wellness diary for asthma management combined with Bluetooth pulse oximeter and manual peak flow measurements; and a questionnaire for ecological assessment of distress during fertility treat-ment. Results are presented of user experiences with the self-reporting applica-tion and the capture of physiological measurements in the case of the asthma diary project and the findings from a phone audit at an early stage of design in the case of the in vitro fertilisation (IVF) study. Issues raised by ethics commit-tees are also discussed. It is concluded that the optimal adoption of Smartphone self-reporting applications will require a good appreciation of user and ethics panel requirements at an early stage in their development, so that the correct de-sign choices can be made.